Clinical comparative study regarding interrupted and uninterrupted dabigatran therapy during perioperative periods of cryoballoon ablation for paroxysmal atrial fibrillation. Issue 2 (August 2019) - Nakamura, Rena; Okishige, Kaoru; Shigeta, Takatoshi; Nishimura, Takuro; Kurabayashi, Manabu; Yamauchi, Yasuteru; Sasano, Tetsuo; Hirao, Kenzo
Highlights: Continuous direct oral anticoagulant (DOAC) administration throughout atrial fibrillation ablation is still controversial. We compared interrupted DOACs and uninterrupted dabigatran throughout the ablation. Uninterrupted dabigatran significantly reduced risk of silent stroke. There were no significant differences in bleeding events. Abstract: Background: Catheter manipulation in the left-sided heart is known as a risk for cerebral embolisms (CEs). However, anticoagulation therapy is terminated before catheter ablation (CA) of atrial fibrillation (AF) concerning adverse bleeding events. Little is known whether uninterrupted direct oral anticoagulants (DOACs) during perioperative period of CA could render the ablation procedure safer and reduce the incidence of CEs compared to interrupted DOACs. The aim of this study was to investigate the safety and usefulness of uninterrupted dabigatran during the periprocedural period for CA of AF. Methods: We included 333 patients with paroxysmal AF undergoing cryoballoon CA (CBA). They were prospectively divided into 2 groups based on whether DOACs were interrupted on the day of the CA (Group A, n = 228) or dabigatran was not interrupted throughout perioperative period (Group B, n = 105) in a non-randomized fashion. When the Group B patients had taken other DOACs rather than dabigatran before assignment, we changed those DOACs to dabigatran. Brain magnetic resonance imaging (MRI) was undertaken on the following day of the CA. Serious bleeding event cases were excluded from the study. Results: The baseline characteristics including the CHADs2 score did not exhibit any significant differences between the groups. The brain MRI revealed an acute CEs in 82 patients, and was significantly higher in Group A than B (29% vs. 13%, respectively, p < 0.01). There were no significant differences regarding the bleeding events (7% vs. 4%, respectively, p = 0.62). Conclusion: Uninterrupted dabigatran therapy during the CBA of paroxysmal AF could significantly reduce the incidence of CEs.